45.7k views
5 votes
Help me please I am so confused...

Help me please I am so confused...-example-1

1 Answer

6 votes

Step-by-step explanation:

"b2" was replaced by "b^2". 1 more similar replacement(s).

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

a-((h*(b^2+b^2))/(2))=0

Simplify: hb2 /1

a - hb2 = 0

Factoring: a-hb2

Theory : A difference of two perfect squares, A2 - B2 can be factored into (A+B) • (A-B)

(A+B) • (A-B) =

A2 - AB + BA - B2 =

A2 - AB + AB - B2 =

A2 - B2

AB = BA is the commutative property of multiplication.

- AB + AB equals zero and is therefore eliminated from the expression.

a1 is not a square

Binomial can not be factored as the difference of two perfect squares

a - hb2 = 0

Solve :a-hb2 = 0

I think

User Phil Helix
by
4.8k points